Sistem Smart Urban Gardening Berbasis Internet of Things - Budi Herdiana; Muhammad Habibi Barkatulah (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2018)
Abstract - The need for the development of technology plays an important role as the more advanced times make us have to keep up with technological advances, this plant activists have the desire to plant hydroponic methods, one of which can be used is the Nutrient Film Technique system. Basically hydroponic plants need supervision and special attention to make hydroponic plants grow as desired. So we need a special way to find out the pH of water in plants, nutrients in plants, temperature and air humidity in plants is needed by people who will plan farming activities, in the future by knowing the information from the sensors used, the community can prepare some things that need to be prepared as anticipating the possibilities that will occur. In this study, the Smart Urban Gardening tool uses the hydroponic method with the Internet Of Things based Nutrient Film Technique system, where there will be several parameters such as pH on automatic controlled water, nutrients on water to be measured, temperature and humidity, these parameters will be sent to the webserver via smartphone, in this study webserver is used, namely the keyboard as a data server to see the results of sensor readings, after the data has been sent successfully it will then be displayed on two interfaces namely android and website applications. The application used can determine the state of water ph in plants and water nutrients in plants and the temperature for the pH of the plants used are in the range 6.5 to 7.0, From the data that can be taken as a result, the pH obtained in plant water is 6 , 6 and stated to be in the appropriate rangeof plants, then the nutritional value obtained is 7.65 for temperatures of 25.9 and humidity of 56.8, so this tool can be used for hydroponic plants. Keywords : Internet Of Things, android, iserius board, Sistem Otomatis, Nutrient Film Technique.